HUBUNGAN RIWAYAT PEMBERIAN ASI EKSKLUSIF DAN IMUNISASI DASAR LENGKAP DENGAN KEJADIAN STUNTING PADA BALITA USIA 24-59 BULAN DI WILAYAH KERJA UPTD PUSKESMAS KUTA UTARA - Ni Ketut Trisnawati; Putu Mastiningsih; Pande Putu Indah Purnamayanthi; Ni Made Egar Adhiestiani (Jurnal Maternitas Kebidanan, 2024)
Stunting is a problem of imbalance in nutritional intake which is closely related to the First 1000 Days of Life (HPK) period. Basic causes include socio-economic factors such as family income, maternal education, and employment. Indirect causes include feeding practices and food security, access to health services, and household environmental sanitation. Meanwhile, direct causes of stunting include food intake and infectious diseases. The aim of this research is to determine the relationship between the history of exclusive breastfeeding and complete basic immunization with the incidence of stunting in toddlers aged 24 - 59 months at the Working area UPTD Puskesmas Utara Kuta.This research uses an observational analytical quantitative research method which uses a retrospective approach, namely observing events that have occurred with the aim of looking for factors related to the cause. The sampling technique in this study used a total sampling technique, namely all mothers with stunting toddlers aged 24 - 59 months would be sampled, namely 16 people. Data were analyzed using analysis using the Chi Square Test.The results of the analysis using the Chi Square test with statistical test results from 16 respondents obtained a p-value of 0.003. These results indicate that H0 is rejected and Ha is accepted, which means there is a significant relationship between complete basic immunization and the incidence of stunting in toddlers aged 24-59 months at the Working area UPTD Puskesmas North Kuta. Based on the results of this research, it is hoped that mothers can prevent the incidence of stunting by providing exclusive breast milk. and complete basic immunization.